The use of nitrogen fertilizer in bean crops - Caballero, Segundo Urquiaga; Libardi, Paulo L.; Reichardt, Klaus; Matsui, Eiichi; Victória, Ricardo L. (Pesquisa Agropecuaria Brasileira, 2014)
The efficiency of nitrogen in beans (Phaseolus vulgaris, L) cv. Carioca was studied in an Oxic Paleudalf soil, in Piracicaba, SP, Brazil, in five periods (6,26,46, 66 and 86 days after germination-DAG). Zero and 42 kg of N/ha were applied, using ammonium sulphate with 56.111% of 15N atoms in excess. This fertilization took place in two stages: 1/3 six DAG and the rest 26 DAG. The plant population was of 250,000 per hectare. Each sample comprised branches + leaves, roots, pods and whole plants. Such samples were analysed for total N content (semi-microkjeldahl method) and N isotopic composition (Dumas method), using an Atlas Variant CH-4 mass spectrometer. The following conclusions were obtained: a) the source of N used significantly increased the production; b) the percentage of N in the plant, obtained from the fertilizer, varied (p = 0.05) as concerned to sampling time, but not among plant parts within each sample; c) the maximum efficiency in N fertilizer utilization (75.9%) was observed during the stage of higher pod development; and d) the grains obtained 16.4 kg/ha of N from the fertilizer and used efficiently 38.9%.